Transvenous extraction of pacemaker leads via femoral approach using a gooseneck snare - KEPEZ, ALPER; ÖZBEN SADIÇ, BESTE (URBAN & VOGEL, 2021)
Background. The growing problem of endocardial lead infections and leadmalfunctions has increased interest in percutaneous lead-removal technology. Transvenous lead extraction (TLE) via simple manual traction (SMT) is the first-line therapy. When SMT is not successful, TLE from the femoral vein using a gooseneck snare (GS) with a radiofrequency ablation catheter (RFAC) may be an alternative option. The aim of our study was to evaluate the success rate of transvenous extraction of chronically implanted leads via the femoral approach using a GS with RFCA in cases of failure with SMT.Methods. The study included 94 consecutive patients who were referred for lead extraction due to pocket erosion and infection (71 patients) and to lead malfunction (23 patients). Initially, SMT was attempted for all patients. If SMT was not successful, patients underwent TLE using a GS with RFAC. Results. Leads were extracted successfully with SMT in 34 patients (54 leads), while 60 patients (83 leads) underwent TLE using a GS with RFAC. The mean indwelling time of the leads was longer in the femoral approach with GS (87.5 +/- 37.9 vs. 31.3 +/- 25.8 months; p< 0.001). The procedural success rate was 96.7% in the femoral approach with GS. A preceding implantation lead duration of >51 months predicted an unsuccessful SMT necessitating alternative TLE using a GS with RFAC with 86% sensitivity and 78% specificity (p< 0.001). Conclusion. Transvenous lead extraction via the femoral approach using GS with RFAC may be an alternative approach to SMT with a high success rate, especially when the indwelling time of the leads is long.
Keywords: Femoral vein; Endocardium; Radiofrequency ablation; Implantable cardioverter defibrillators; Cardiac pacemakers; CARDIOVERTER-DEFIBRILLATOR LEADS; ESC GUIDELINES; LASER SHEATH; ASSOCIATION; EXPERIENCE; MANAGEMENT; OUTCOMES; REMOVAL; SOCIETY; PATIENT